Work Culture in Indian Organizations - Kapoor, Deep (Ushus Journal of Business Management, 2021)
Work is a source of sustenance to human beings. The environment where the person works has a lot of effect on the efficiency and effectiveness. In a layman’s language we can call this environment along with the processes working in it as the ’Work Culture’. With the opening up of Indian economy and the flourishing of knowledge based industries in India, this environment of work has considerably changed and it has a marked influence on the social lives of the people working in these kinds of industries. As these industries are located mostly in big/metropolitan cities and affects educated urban middle/upper class generally, this paper will be somewhat skewed towards these class of people working mostly in large organizations. I will also concentrate on defining work culture, on types of work culture, on the impact of society on work culture, on emerging work culture and finally focussing on the knowledge based industries.